The Two - Variable (G/ G ,) (1/ G) - Expansion Method for Solving Nonlinear Dynamics of Microtubles - A New Model (Global Journal of Science Frontier Research, 2015)
In this paper, we employ the ( )-expansion method to find the exact traveling wave solutions involving parameters of nonlinear dynamics of microtubulesa New Model . When these parameters are taken to be special values, the solitary wave solutions are derived from the exact traveling wave solutions. It is shown that the proposed method provides a more powerful mathematical tool for constructing exact traveling wave solutions for many other nonlinear evolution equations.
Keywords: The ( )-expansion method; Nonlinear dynamics of microtubules; Traveling wave solutions; Solitary wave solutions; Kink-anti kink shaped